2020
DOI: 10.1111/bdi.12859
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and tolerability of adjunctive modafinil/armodafinil in bipolar depression: A meta‐analysis of randomized controlled trials

Abstract: Objective The aim of this study was to evaluate the efficacy and safety of the dopaminergic‐enhancing agent modafinil/armodafinil (MoArm) as adjunctive treatment for bipolar depression. Methods A comprehensive search of major electronic databases was conducted to identify randomized controlled trials (RCTs) of adjunctive MoArm that included patients with bipolar I (BP‐I) or bipolar II (BP‐II) depression. Data for response/remission and all‐cause discontinuation were analyzed. Effect size was summarized by rela… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 52 publications
1
10
0
Order By: Relevance
“…Likewise, treating menopausal fatigue with armodafinil was associated with improvement in depressive symptoms, insomnia, cognitive function, and total scores of the MENQOL scale [23]. In the meantime, a current meta-analysis revealed that use of armodafinil as an adjunctive treatment for depressive and bipolar disorders improves responsiveness to antidepressants [51]. Altogether, fatigue experienced by peri-and postmenopausal women may alter psychological wellbeing, and proper management of fatigue may be essential to prevent the development of chronic fatigue syndrome and mood disorders.…”
Section: Discussionmentioning
confidence: 88%
“…Likewise, treating menopausal fatigue with armodafinil was associated with improvement in depressive symptoms, insomnia, cognitive function, and total scores of the MENQOL scale [23]. In the meantime, a current meta-analysis revealed that use of armodafinil as an adjunctive treatment for depressive and bipolar disorders improves responsiveness to antidepressants [51]. Altogether, fatigue experienced by peri-and postmenopausal women may alter psychological wellbeing, and proper management of fatigue may be essential to prevent the development of chronic fatigue syndrome and mood disorders.…”
Section: Discussionmentioning
confidence: 88%
“…However, in two further doubleblind RCTs of adjunctive armodafinil in bipolar I depression, although armodafinil reduced depressive symptoms to a greater extent than placebo, it did not separate from placebo in the primary efficacy outcomes in either study [72,73]. A recent meta-analysis combining these studies found that compared with placebo, augmentation with modafinil or armodafinil was associated with significantly greater treatment response and remission, encouraging further studies that delineate subtypes of bipolar depression responsive to these novel dopamine enhancing agents [68].…”
Section: Modafinil and Armodafinilmentioning
confidence: 99%
“…The wakefulness-promoting agent modafinil and its longer lasting R-enantiomer (armodafinil) both act to inhibit dopamine-reuptake and have a potential adjunctive role in bipolar depression [68]. One placebo-controlled trial examining adjunctive modafinil at doses of 100 mg-200 mg/day in bipolar depression found significantly greater improvement in depressive symptoms in the modafinil group at week 2, maintained through to week 6 [69].…”
Section: Modafinil and Armodafinilmentioning
confidence: 99%
“…Moreover, we also replicated the results of a more recent meta-analysis showing that, compared to placebo, augmentation with modafinil/armodafinil (MoArm) as adjunctive treatment for bipolar depression was associated with significantly greater rates of treatment response, with the all-cause discontinuation not differing from placebo and no evidence of mood switch or suicide attempts on MoArm treatment. 72 Based on the above, in addition to using psychostimulants in comorbid ADHD and BD, it seems that using psychostimulants (and stimulant-like drugs) as an add-on to standard treatment in resistant bipolar depression may well have a place in clinical practice, not only in in-patients but in out-patients as well. Improvement in the symptoms of resistant bipolar depression translates into improvement in patient quality of life, decreased carer and family burden, lower cost for the health service and fewer lost days at work.…”
Section: Implications For Clinical Practicementioning
confidence: 99%